Accidental hypothermia. Issue 7543 (23rd March 2006) - Epstein, Elliot; Anna, Kiran
Abstract : Hypothermia is a life threatening condition, and management can be challenging, with little robust evidence to support the various treatments. This article should help doctors to understand the condition better